Not all “distractor” tags are created equal: using a search asymmetry to dissociate the inter-trial effects caused by different forms of distractors - Lleras, Alejandro; Buetti, Simona (Frontiers in Psychology, 2014)
In a typical pop-out task, there is one target and a varying number of distractor stimuli. Now imagine a target-absent display in the context of a pop-out task: all items are identical, and it is decidedly easy to conclude that all items in the display are distractors, precisely because there is no target to select on that display. One may be tempted to say that, as far as the attention system is concerned, these two types of distractors are the same: target-present distractors and target-absent distractors. The present study proposes that this is actually not the case. Target-absent distractors can sometimes produce inter-trial effects that their close-cousins, the target-present distractors, cannot. We used a letters/numbers categorical oddball task to demonstrate this difference. The results are interpreted in the context of recent findings in cognitive neuroscience as well as cognitive modelling.